Climate Change as a Threat to Environmental Safety: International Legal Regulation - Sharaievska, Tetiana (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The article is devoted to the study of international legal regulation of environmental safety with regard to climate change. It is established that indicated problem is common to the entire mankind and requires effective and advancing response and determines the need to replenish national legislation with international and European ecologico-legal models for regulation of environmental relations. It is analysed that modern development of legislation of Ukraine in the field of environmental safety should be carried out considering the processes of globalization. The conclusion is drawn that deepening of cooperation between the countries worldwide for overcoming the negative impact of climate change on mankind and environment as a whole assumes important significance.